2003
DOI: 10.1128/jvi.77.2.1306-1315.2003
|View full text |Cite
|
Sign up to set email alerts
|

Viability of a Drug-Resistant Human Immunodeficiency Virus Type 1 Protease Variant: Structural Insights for Better Antiviral Therapy

Abstract: Under the selective pressure of protease inhibitor therapy, patients infected with human immunodeficiency virus (HIV) often develop drug-resistant HIV strains. One of the first drug-resistant mutations to arise in the protease, particularly in patients receiving indinavir or ritonavir treatment, is V82A, which compromises the binding of these and other inhibitors but allows the virus to remain viable. To probe this drug resistance, we solved the crystal structures of three natural substrates and two commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 66 publications
4
121
0
Order By: Relevance
“…Although the peptides used for crystallization span a slightly different region of the cleavage site (P5 to P5Ј and P4 to P6Ј), these differences are likely to have minimal or no effect on the bound conformation of the substrate. From our previous experience with to determine substrate complexes with HIV protease (38,39,49), the P5 and P5Ј residues usually have no contact with the protease and are often disordered in the electron density. Thus, the presence or absence of P5 or P6Ј is unlikely to impact how the substrate is packed in the active site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the peptides used for crystallization span a slightly different region of the cleavage site (P5 to P5Ј and P4 to P6Ј), these differences are likely to have minimal or no effect on the bound conformation of the substrate. From our previous experience with to determine substrate complexes with HIV protease (38,39,49), the P5 and P5Ј residues usually have no contact with the protease and are often disordered in the electron density. Thus, the presence or absence of P5 or P6Ј is unlikely to impact how the substrate is packed in the active site.…”
Section: Resultsmentioning
confidence: 99%
“…Crystals were grown by the hanging drop, vapor diffusion method as previously described (38,39,49). Stock solutions (25 mM) of substrate peptides used for cocrystallization were dissolved in refolding buffer rather than in dimethyl sulfoxide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept has been successfully used in designing robust protease inhibitors and in predicting the sites of drug-resistant mutations. [12][13][14] Additionally, recent studies examined substrates from patient samples and found that the sequences of the substrates coevolved with major drug-resistant mutations in the protease. 15,16 These findings suggest that for resistant protease variants, there is an alteration of substrate specificity that is selected for in the coevolving substrate sites.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of HIV-1 protease in complex with substrates and inhibitors indicate that the drug-resistant mutants of this enzyme have altered molecular recognition abilities; they still recognize the enzyme's substrates but binding to inhibitors is disrupted. [9][10][11][12] The mechanisms involved in substrate recognition and binding of these drug-resistant mutants have yet to be fully elucidated. To gain insight into these processes, an improved understanding of which residues dictate substrate binding specificity and how these sites evolve with the emergence of drug resistance is required.…”
Section: Introductionmentioning
confidence: 99%